REVIEW AND COMPARISON OF MULTIPLE DIGITAL SIGNATURES - Nelasa, G. V.; Dozorenko, I. S. (Radio Electronics, Computer Science, Control, 2011)
Several batch verication multiple digital signatures are reviewed in this paper. These schemes use only one verification instead of several verifications. Weakness of these schemes is also pointed out. The schemes were compared by the defined criterions.